Distant Realization of Valency of Compound Component - Klyuchenovich, Sergey (Bulletin of Yerevan University B: Philology, 2021)
The valency of a component with verb semantics included in a German substantive compound can receive a distant realization in the text. This process has a direct effect on text formation. The study is based on modern fiction, mass media texts, and legislative acts. Distantly explicated arguments can be represented by separate words or built in the structure of another compound. In the case of filling several valencies, a combination of distant realization of some arguments and inclusion of other arguments in the direct syntactic environment of the compound is possible. A text indication of distant realization of an argument is possible, which is a specific characteristic of the legislative discourse.
Keywords: compound; component with verb semantics; external valency; distant valency realization